Transformational Leadership Impact on Employee's Motivation: A Comparative Study of National and Multinational Pharmaceutical Companies in Pakistan - Fawad Khan (Theory, Methodology, Practice, 2023)
Pakistan, being a developing economy, is in continuous transition to achieve its targeted developmental goals. In this regards, prime attention to the industrial sector is gaining importance. In the industrial sector, the pharmaceutical industry holds a significant role in meeting the national medicine demands and contributing to the country’s economic growth at the same time. Promoting the manufacturing sector not only requires appropriate leadership but also a pool of motivated workers who can achieve the objectives. This paper investigates the effects of transformational leadership on employees’ motivation in the pharmaceutical sector of Pakistan. Both local and multinational firms are taken into consideration. Data collected through a structured questionnaire from 503 respondents is analysed using SPSS 25. Results show that the application level of transformational leadership is higher in multinational companies as compared to the native companies. However, the impact of transformational leadership on employees’ motivation is almost the same for both local and multinational companies.